(untitled) (Economic studies journal, 2025)
This study aims at finding out the impact of organizational genes on the organizational creativity from the perspective of employees at Al-Wahda Bank in Sirte. The researcher used a comprehensive census approach to collect data, distributing questionnaires to all (45) employees at the bank under study. A total of (43) questionnaires were returned, and two were excluded as they were not suitable for analysis, resulting in a response rate of (95.5%) .The Statistical Package for the Social Sciences (SPSS) was used to process the collected data, employing descriptive and inferential statistical methods such as the arithmetic mean, standard deviation, linear regression analysis, and other statistical analyses.The study concluded with several key findings, most notably the existence of a statistically significant effect of organizational genes and their various dimensions(decision-making, incentives, organizational structure, and information) on organizational creativity from the employees’ perspective at Al-Wahda Bank. The study also provided a set of recommendations that may assist planners and policymakers in Libyan banks in establishing and developing encouraging systems and a suitable organizational climate to enhance and elevate the level of organizational creativity among their staff.